Leakage of periplasmic proteins from Escherichia coli mediated by polymyxin B nonapeptide. - Dixon, R A (1986)
The effects of polymyxin B and polymyxin B nonapeptide (PMBN) on cell envelope integrity in Escherichia coli were compared. Both compounds caused loss of proteins from E. coli K-12 3300(pBR322), although PMBN released less protein than did polymyxin B. The origin of the released protein was determined both by polyacrylamide gel electrophoresis and by using specific enzyme markers (beta-lactamase in periplasm, beta-galactosidase in cytoplasm). The proteins released by both compounds were derived principally from the periplasm, accompanied in the case of polymyxin B by a low level of cytoplasmic proteins. Although polymyxin B and PMBN both caused release of periplasmic proteins, the individual proteins released by the compounds differed. The periplasmic fraction contained six principal polypeptides with molecular weights between 62,000 (polypeptide 1) and 29,000 (polypeptide 6). Polypeptide 6 was identified as the pBR322-encoded beta-lactamase, but the other proteins were not specifically identified. Polymyxin B caused considerable release of polypeptides 1, 2, and 5 with some release of polypeptides 4 and 6. PMBN released polypeptide 1 (trace), 3, 4, and 6 (trace). Scanning electron microscopy showed that polymyxin B and PMBN both caused surface damage in E. coli. However, polymyxin B produced greater morphological changes than PMBN.